2022
DOI: 10.3390/ijerph19052885
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Neuroticism and Non-Suicidal Self-Injury Behavior among College Students: Multiple Mediating Effects of Emotion Regulation and Depression

Abstract: Background: Non-suicidal self-injury (NSSI) behavior among college students is a focus of attention in current society. In the information era, the Internet serves as a public health concern and as an effective pathway for prevention. In order to reduce NSSI behavior, we explore its influence factors, especially the relations between neuroticism, emotion regulation (ER), depression, and NSSI behavior. Methods: A total of 450 college students were surveyed with the Big Five Inventory-2, Emotion Regulation Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Other studies, more focused on the relationship between emotional intelligence and emotional distress [ 28 ], showed that high levels of emotional attention have been related to greater emotional distress [ 28 ]. Regarding the dimension of emotional repair, the results obtained by different researchers are in the same direction as those found in the present investigation [ 27 , 32 ], although these studies do not analyze the role mediator of negative affect in the relationship between neuroticism and emotional intelligence, so our results are revealing at an explanatory and empirical level in this sense. This work probably supports the results of Aluja [ 49 ] on the neuroticism construct, allowing us to know how its components operate psychologically (mediating or moderating) in our case, in the explanation of the relationship between neuroticism and emotional intelligence.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Other studies, more focused on the relationship between emotional intelligence and emotional distress [ 28 ], showed that high levels of emotional attention have been related to greater emotional distress [ 28 ]. Regarding the dimension of emotional repair, the results obtained by different researchers are in the same direction as those found in the present investigation [ 27 , 32 ], although these studies do not analyze the role mediator of negative affect in the relationship between neuroticism and emotional intelligence, so our results are revealing at an explanatory and empirical level in this sense. This work probably supports the results of Aluja [ 49 ] on the neuroticism construct, allowing us to know how its components operate psychologically (mediating or moderating) in our case, in the explanation of the relationship between neuroticism and emotional intelligence.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding emotional regulation, we must highlight that it has proven to be one of the most important tools both to reduce and control negative emotions [ 32 ]. The recent study by Yildirim et al [ 27 ] with a sample of non-clinical adolescents shows that both attention and emotional clarity play a very important role in emotional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the parenting style may be another risk factor for adolescent NSSI ( Gray et al, 2022 ). An excessively strict parenting style will affect children’s inferiority and rebellious psychology, including anxiety, depression, and NSSI ( Liao et al, 2022 ). This finding suggests that parenting style may affect the relationship between adolescents’ emotions and NSSI.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…When undergraduate students face adversity or passive interpersonal relationships, if they suppress their emotions for a long time without being able to regulate them, they are prone to emotional disorders that affect their physical and mental health. In more serious cases, irreversible consequences such as suicide and antisocial behavior will be induced, while those who are able to use emotion regulation strategies flexibly and appropriately tend to have better interpersonal relationships and social adaptability (Liao et al, 2022). Thus, emotion regulation in undergraduate students is of great research importance, both clinically and in theoretical guidance.…”
Section: Introductionmentioning
confidence: 99%